Water Treatment for Purification from Cyanobacteria and Cyanotoxins - Hiskia, Anastasia E; Triantis, Theodoros M; Antoniou, Maria G; Kaloudis, Triantafyllos; Dionysiou, Dionysios D (John Wiley & Sons, 2020)
Toxigenic cyanobacteria are one of the main health risks associated with water resources. Consequently, the analysis, control, and removal of cyanobacteria and cyanotoxins from water supplies is a high priority research area. This book presents a comprehensive review of the state-of-the-art research on water treatment methods for the removal of cyanobacteria, taste and odor compounds, and cyanotoxins. Starting with an introduction to the subject, this book offers chapters on cyanotoxins and human health, conventional physical-chemical treatment for the removal of cyanobacteria/cyanotoxins, removal of cyanobacteria and cyanotoxins by membrane processes, biological treatment for the destruction of cyanotoxins, and conventional disinfection and/or oxidation processes. Other chapters look at advanced oxidation processes, removal/destruction of taste and odour compounds, transformation products of cyanobacterial metabolites during treatment and integrated drinking water processes.